THE EFFECTIVENESS OF THINK ALOUD STRATEGY IN TEACHING READING COMPREHENSION OF NARRATIVE TEXTS - Daria, Oktavia; Salam, Urai; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of the research is to find out whether Think Aloud strategy is effective or not in teaching reading comprehension of narrative text. This research used pre-experimental design with pre-test, post-test, and three times of treatments. The participants of this research were 39 students of class X MIA at SMA Santo Fransiskus Asisi who were chosen by using cluster random sampling. The data were collected using the measurement technique and the tool of data collection was a written test. The research findings showed that the mean score of the students’ pre-test was 59.28 while the post-test was 77.53. The increase of the students’ mean score of pre-test and post-test was 18.25. It showed that the ability of the students increased after the treatment was conducted. The t-test was higher than the t-table (10.08 > 1.686). The result of the effect size (ES) was 1.51, which was categorized as a strong effect (ES > 0.50). It showed that the alternative hypothesis was accepted. It can be concluded that the Think Aloud strategy is strongly effective to teach students’ reading comprehension of narrative text.Keywords: Reading Comprehension, Narrative Text, Think Aloud Strategy